Potential Use of WT1 as a Diagnostic and Therapeutic Marker of Acute Myeloid Leukemia: A Review - Almitra Rindiarti; Yeremia O'neal Harsono (Universitas Bio Scientia Internasional Indonesia, 2026)
Acute myeloid leukemia (AML) is a heterogeneous malignancy characterized by uncontrolled proliferation and impaired hematopoietic differentiation of myeloid lineage with rapid disease progression. Among the various biomarkers studied, Wilms’ tumor 1 (WT1) is a widely expressed gene in AML, making it an attractive biomarker candidate for diagnosis and minimal residual disease (MRD) monitoring. This review evaluates the potential of WT1 as an effective diagnostic biomarker and the current detection methods, highlighting the advantages and limitations of the current gold standard, RT-qPCR, and exploring potential alternative approaches, such as ELISA and antibody-based flow cytometry, for its clinical applicability. Using public gene datasets, bioinformatic analysis further supports WT1’s overexpression in AML, though with varying levels across subtypes, suggesting its potential as part of a multimodal diagnostic plan rather than a standalone marker. Beyond diagnostics, WT1 is also a promising therapeutic target, with peptide and dendritic cell vaccines, as well as TCR-engineered T cells, demonstrating encouraging clinical outcomes. Next-generation strategies, including CAR-T cells, bispecific T-cell engagers, and mRNA vaccines, are advancing preclinical and early clinical studies. Together, these findings highlight WT1 as both a biomarker and a therapeutic target, with future integration into precision medicine likely to improve AML detection, risk stratification, and treatment.